HYDROGRAPHY OF THE INSHORE WATERS OF MADRAS COAST FOR THE PERIOD JANUARY 1973 TO MARCH 1975 - Muthuswamy, S (Indian Journal of Fisheries, 2011)
Wa,ter samples were collected from the inshore surface water's offMadras dty, wher'e the depth ranged fJ'OIU 20 to 30 metres, ,and the changes insalinity, pH, dissolved-oxygen content, phosphate, nitrite, silicate and nit.faJtewere monitered fr'Om J'anuary 1973 to Ma:roh 1975. Observations on the seasurface temperature were made from an arela adjoining ,the Madras Harbour.The variations observed were subje,caed 1;0 smoothing analysis and are depictedin figures 1 and 2.